Caracterización del efecto de los aditivos antidesgaste de varias marcas del mercado nacional en un aceite SAE20W-40 - Ochoa Fonseca, Denisse Estefanía (2017)
There is an extensive variety of products on the market that offer to reduce the wear between elements that work to friction in a mechanism, being its performance unknown or not considered for the buyer. The present work consists of a research on the effect of anti-wear additives in an SAE oil, for which a machine was designed that allows to carry out studies of wear according to the method Timken block on ring, under the norm ASTM 2782-02. Which served as an instrument to carry out tests that allowed to characterize the effect of the additives put to test. In this way, a theoretical framework is included that reveals the basic concepts of friction, wear, lubrication, lubricating oils, additives, and parameters that are linked to the tribology, science to which our research is focused. These arguments are presented on the basis of foundations supported by their respective source. The methodology that was used in the development of this research was experimental type with which the wear was measured in a fixed specimen that was in contact with a mobile of the same material. A total of twelve trials were performed with Kendall oil plus an anti-wear additive, subjected to three different loads, in a time of six minutes. The results obtained from this practice allow to make a comparison wear vs. charge and temperature vs. load, generating the following information: Qualitor decreased wear by 46%, Target increased wear by 8%, Liqui Moly decreased wear by 14%.